Effect of exogenous additives on heavy metal passivation and nitrogen retention in pig manure composting - Ziqi WANG; Guotao SUN; Jiamin WANG; Gongshe YANG (Frontiers of Agricultural Science and Engineering)
● Research on heavy metal passivation and nitrogen emissions is necessary for the pig industry. ● Mechanism of heavy metal passivation and nitrogen retention by different additives was introduced. ● Development and prospect of metal passivation, nitrogen preservation technology were discussed. The widespread use of feed additives in intensive and large-scale pig farming has resulted in high levels of heavy metals in pig manure. The long-term application of organic fertilizers containing high levels of heavy metals leads to the accumulation of heavy metals in the soil, which not only causes heavy metal pollution in the soil, and also affect food safety and endanger human health. Composting is an economical and effective technical measures to achieve environmentally-sustainable treatment of pig manure and is a practical method to reduce the problem of heavy metals and to improve the resource value of pig manure. The composting process is accompanied by high temperatures and the production and emission of gases, and also lead to changes in the nitrogen content of the compost and provide opportunity for heavy metal passivation additives. This paper summarizes the forms and types of heavy metals present in pig manure and reviews the progress of research as well as the techniques and problems of in the composting process, and provides recommendations for research on heavy metal passivation and nitrogen retention in pig manure composting.